EDUCATION SOCIAL MEDIA WISELY IN KARANGTARUNA BENDA BARU DESA BENDA BARU DISTRICT PAMULANG SOUTH TANGERANG CITY: EDUKASI BERSOSIAL MEDIA DENGAN BIJAK DI KARANGTARUNA BENDA BARU DESA BENDA BARU KECAMATAN PAMULANG KOTA TANGERANG SELATAN - Agus Wiranto; Intan Kumalasari; Rifky Novrian Kahar; AA Kurniawan; Nurfiqih Nurfiqih (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Advances in technology and information are an inseparable part of globalization experienced by every nation. Social media is now increasingly accessible to everyone. There are no restrictions or distinctions for each group to access social media, both for the educated group and the less educated group. All have equal access to express their thoughts in the public sphere. The rapid development of technology and information if it is not balanced with education to the public to use it wisely will be very dangerous. Unlike when someone wants to write in a magazine or newspaper, he will get strict supervision from the editors. Therefore, this community service offers a solution by providing education by providing understanding to the community, especially the Karangtaruna youth in Benda Baru Pamulang, South Tangerang to use social media wisely. So it is hoped that this training and education can influence the community to always use the internet wisely both in the mass media and on social media. So it is hoped that in the future young people will be able to use social media wisely, encourage the youth community to have a sense of pride in participating in the National Mental Revolution Movement or Gerakan Nasional Revolusi Mental (GNRM) through their respective social media and grow grassroots movements to spread Mental Revolution content involving the younger generation. In accordance with Impres No. 12 of 2016 concerning the National Movement for Mental Revolution (GNRM)